15-Deoxy-Δ12, 14-prostaglandin J2 induces p53 expression through Nrf2-mediated upregulation of heme oxygenase-1 in human breast cancer cells. (September 2014) - Kim, D. H.; Song, N. Y.; Kim, E. H.; Na, H. K.; Joe, Y.; Chung, H. T.; Surh, Y. J.
Abstract: Heme oxygenase-1 (HO-1) is a stress-responsive enzyme that has antioxidant and cytoprotective functions. However, HO-1 has oncogenic functions in cancerous or transformed cells. In the present work, we investigated the effects of HO-1 on the expression of p53 induced by 15-deoxy-Δ 12, 14 -prostaglandin J2 (15d-PGJ2 ) in human breast cancer (MCF-7) cells. Treatment of MCF-7 cells with 15d-PGJ2 led to time-dependent increases in the expression of p53 as well as HO-1. Upregulation of p53 expression by 15d-PGJ2 was abrogated by si-RNA knock-down of HO-1. In MCF-7 cells transfected with HO-1 si-RNA, 15d-PGJ2 failed to induce expression of p53 as well as HO-1. In addition, HO-1 inducers enhanced the p53 expression. We speculated that iron, a by-product of HO-1-catalyzed reactions, could mediate 15d-PGJ2 –induced p53 expression. Upregulation of p53 expression by 15d-PGJ2 was abrogated by the iron chelator desferrioxamine in MCF-7 cells. Iron released from heme by HO-1 activity is mostly in the Fe 2+ form. When MCF-7 cells were treated with the Fe 2+ -specific chelator phenanthroline, 15d-PGJ2 –induced p53 expression was attenuated. In addition, levels of the Fe-sequestering protein H-ferritin were elevated in 15d-PGJ2 -treated MCF-7 cells. In conclusion, upregulation of p53 and p21 via HO-1 induction and subsequent release of iron with accumulation of H-ferritin may confer resistance to oxidative damage in cancer cells frequently challenged by redox-cycling anticancer drugs.